Effect of collisions on amplification of laser beams by Brillouin scattering in plasmas - Humphrey, K; Trines, R; Fiuza, F; Speirs, D; Norreys, P; Cairns, R; Silva, L; Bingham, R (2013)
We report on particle in cell simulations of energy transfer between a laser pump beam and a counter-propagating seed beam using the Brillouin scattering process in uniform plasma including collisions. The results presented show that the ion acoustic waves excited through naturally occurring Brillouin scattering of the pump field are preferentially damped without affecting the driven Brillouin scattering process resulting from the beating of the pump and seed fields together. We find that collisions, including the effects of Landau damping, allow for a more efficient transfer of energy between the laser beams, and a significant reduction in the amount of seed pre-pulse produced. © 2013 AIP Publishing LLC.